AQUA-SIT, monitorare la qualità dell’acqua in real time - Ioannilli, Maria; Paregiani, Alessandro; Pede, Andrea (GEOmedia, 2009)
AQUA-SIT: a real time water quality monitoring system Two spin-off companies from the Tor Vergata University of Rome are jointly developing an innovative system for real-time monitoring of water quality. The new system integrates a set of sensors, hydrological models, models of pollutant diffusion into the water fl ow and an advanced geographic decision support system. It presents contained investment costs and reduced operational costs, thanks to the centralization of information. Although in a prototypical state, the project has already found a strong interest from some stakeholders in Italy.